High performance and cost-effective supported IrOx catalyst for proton exchange membrane water electrolysis. (20th July 2021) - Min, Xiangping; Shi, Yan; Lu, Zhuoxin; Shen, Lisha; Ogundipe, Taiwo Oladapo; Gupta, Pralhad; Wang, Chi; Guo, Changqing; Wang, Zhida; Tan, Hongyi; Mukerjee, Sanjeevc; Yan, Changfeng
Highlights: IrOx /W-TiO2 was prepared via surface modification and controlled hydrolysis method The catalyst showed an improvement in Ir mass activity compared with unsupported Ir oxides MEA using supported catalyst showed lower HFR than unsupported catalyst Electrolyzer achieved 1.602V@1Acm −2 with only 0.2 mg cm −2 noble metal loading and Nafion 212 membrane. Abstract: A multistep synthesis method is introduced to fabricate high performance IrOx /W-TiO2 catalyst for noble metal reduction in PEM water electrolyzers. The performances of the IrOx /W-TiO2 catalyst for oxygen evolution reaction (OER) are measured in half-cells and single-cells and compared with unsupported IrOx and commercial IrO2 . In half-cell tests, IrOx /W-TiO2 displays an improved Ir mass activity compared with the unsupported IrOx, demonstrating a positive effect of the support material. In single-cell tests, the performance of IrOx /W-TiO2 also exceeds both the unsupported and commercial IrO2 . The cell voltage reaches 1.602V at 1 A cm −2 (Nafion 212) with total noble metal loading less than 0.2 mg cm −2, suggesting that significant Ir reductions are possible by using IrOx /W-TiO2 without sacrificing the cell performance. It also shows improved durability than other unsupported catalysts at reduced Ir loading. In-situ electrochemical test reveals that the performance is associated with the enhanced conductivity of the catalyst layer. Graphical abstract: Image, graphical abstract